Screening prior to Breast Cancer Diagnosis: The More Things Change, the More They Stay the Same - Erica B. Friedman; Jennifer Chun; Freya Schnabel; Shira Schwartz; Sidney Law; Jessica Billig; Erin Ivanoff; Linda Moy; Deborah Axelrod; Amber Guth (International Journal of Breast Cancer)
Purpose. In November 2009, the U.S. Preventative Service Task Force (USPSTF) revised their breast cancer screening guidelines. We evaluated the pattern of screening subsequent to the altered guidelines in a cohort of women. Methods. Our database was queried for the following variables: age, race, method of diagnosis, mass palpability, screening frequency, histology, and stage. Statistical analyses were performed using Pearson’s chi-square and Fisher’s exact tests. Results. 1112 women were diagnosed with breast cancer from January 2010 to 2012. The median age at diagnosis was 60 years. Most cancers were detected on mammography (61%). The majority of patients had invasive ductal carcinoma (59%), stage 0 (23%), and stage 1 (50%) cancers. The frequency of screening did not change significantly over time (P=0.30). However, nonregular screeners had an increased risk of being diagnosed with later stage breast cancer (P<0.001) and were more likely to present with a palpable mass compared to regular screeners (56% versus 21%; P<0.001). Conclusions. In our study, screening behavior did not significantly change in the years following the USPSTF guidelines. These results suggest that women who are not screened annually are at increased risk of a delay in breast cancer diagnosis, which may impact treatment options and outcomes.